Advantages and Disadvantages of Adult Spinal Deformity Surgery and Its Impact on Health-Related Quality of Life. Issue 6 (15th March 2017) - Yoshida, Go; Boissiere, Louis; Larrieu, Daniel; Bourghli, Anouar; Vital, Jean Marc; Gille, Olivier; Pointillart, Vincent; Challier, Vincent; Mariey, Remi; Pellisé, Ferran; Vila-Casademunt, Alba; Perez-Grueso, Francisco Javier Sánchez; et al.
Abstract : Study Design: Prospective multicenter study of adult spinal deformity (ASD) surgery. Objective: To clarify the effect of ASD surgery on each health-related quality of life (HRQOL) subclass/domain. Summary of Background Data: For patients with ASD, surgery offers superior radiological and HRQOL outcomes compared with nonoperative care. HRQOL may, however, be affected by surgical advantages related to corrective effects, yielding adequate spinopelvic alignment and stability or disadvantages because of long segment fusion. Methods: The study included 170 consecutive patients with ASD from a multicenter database with more than 2-year follow-up period. We analyzed each HRQOL domain/subclass (short form-36 items, Oswestry Disability Index, Scoliosis Research Society-22 [SRS-22] questionnaire), and radiographic parameters preoperatively and at 1 and 2 years postoperatively. We divided the patients into two groups each based on lowest instrumented vertebra (LIV; above L5 or S1 to ilium) or surgeon-determined preoperative pathology (idiopathic or degenerative). Improvement rate (%) was calculated as follows: 100 × |pre.–post.|/preoperative points (%) (+, advantages; –, disadvantages). Results: The scores of all short form-36 items and SRS-22 subclasses improved at 1 and 2 years after surgery, regardless of LIV location and preoperative pathology. Personal care and lifting in Oswestry Disability Index were, however, not improved after 1 year. These disadvantages were correlated to sagittal modifiers of SRS-Schwab classification similar to other HRQOL. The degree of personal care disadvantage mainly depended on LIV location and preoperative pathology. Although personal care improved after 2 years postoperatively, no noticeable improvements in lifting were recorded. Conclusion: HRQOL subclass analysis indicated two disadvantages of ASD surgery, which were correlated to sagittal radiographic measures. Fusion to the sacrum or ilium greatly restricted the ability to stretch or bend, leading to limited daily activities for at least 1 year postoperatively, although this effect may subside after another year. Consequently, spinal surgeons should note the effect of surgical treatment on each HRQOL domain and counsel patients about the implications of surgery. Level of Evidence: 4